The Connection of Parents’ Over Protective Perspective with Teenagers’ Self-Adjustment on 7th Grade Students - Saragih, Ruth Liana; Saragih, Melisa; Haqqi, Dhiya Ul (International Journal Labs, 2023)
Background: When the child is present in the family, parents will want their child to be able to develop normally either physically or mentally, so that parents have their own way of treating children. There are parents who give freedom to children on the grounds that children can develop their potential and there are also those who are too afraid that their children are in dangerous or over protective conditions. Aim: This study aims to see the relationship between parents' overprotective perceptions of adolescent self-adjustment in grade VII MTs Darul Ihsan Aceh Besar students. Method: The type of research used in this study is quantitative research because the final data analysis is carried out with statistical tests. The data of this study is in the form of numbers analyzed using statistics processed with the SPSS 2.0 for Windows program. Findings: From the results of data analysis and previous discussions, it can be concluded that there is a very significant positive relationship between the perception of overprotective parents and adolescent self-adjustment in grade VII students in the MTsN Model Banda Aceh. From the results of the analysis, this study has a correlation efficiency of r = 0.593 with a p value = 0.000, meaning that the relationship between the two variables is very significant if p < 0.05. From these results, it shows that the higher the perception of overprotective parents, the higher the adolescent self-adjustment. On the other hand, the lower the perception of overprotective parents, the lower the adolescent self-adjustment in grade VII MTsN Model Banda Aceh students.